419 Integration of Trainees with Mobility Impairment in Neurological Surgery. (April 2023) - Lawrence, Jesse D.; Konrad, Peter; Sedney, Cara L.
Abstract : INTRODUCTION: Increasing attention has been paid to diversity amongst neurosurgical trainees in recent years; but representation of individuals with mobility impairment within neurosurgical training has not been previously demonstrated. METHODS: A trainee with mobility impairment (JL) matriculated to neurosurgical residency in 2017 with programmatic and institutional support. Prior to matriculation he had independently developed standing wheelchairs and operating room protocols. Upon matriculation, a careful needs assessment was performed with the assistance of JL and the university ADA officer and accommodation recommendations were provided. These consisted of generally minor procedural or equipment alterations, including hand controls for surgical devices, cord covering mats in the operating rooms, minor changes to scrub stations and call room, parking access, etc. Minor iterative technique guidance was provided with respect to body mechanics and adaptive equipment which was not demonstrably different than that provided to other residents (eg left hand dominant residents). RESULTS: The trainee has successfully performed in all roles of neurosurgical residency, including the chief resident role, with no alteration of duties, expectations, or assignments. In regards to adaptive equipment, no one solution could be considered ideal for all situations. Specifically, operating room adaptations needed to optimize positioning and mobility while bedside adaptations needed to optimize ease of access and low profile. CONCLUSIONS: Integration and training of individuals with mobility impairment can be successful with minor procedural and equipment alterations, even in a small program with relatively limited resources. This experience demonstrates feasibility and provides a blueprint for other institutions and applicants with mobility impairment who desire to pursue neurosurgical training.